In the kitchen utensils, tools and equipment [videorecording] - Scoglio, Stephen; Video Education America (Indianapolis, IN VEA (Video Education America), 2010)
"Chef Hemi Reidy takes us inside the restaurant kitchen where he weaves his magic for the daily dining pleasure of customers, and presents a lively and comprehensive look at using all sorts of tools, utensils and equipment in the kitchen."
VCD
Keywords: Kitchen utensils; Cooking -- Equipment and supplies